2019
DOI: 10.1177/2158244018821758
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Early Childhood Teachers’ Perceptions of a Preschool Yoga Program

Abstract: Background Yoga for young children has become a growing area of interest in early childhood settings across the United States (Schwind et al., 2017). With an emphasis on stretching, breathing, and mindfulness techniques, yoga has been associated with a decrease in stress and anxiety in young children (Anand & Sharma, 2014). Evidence also suggests that yoga has the ability to improve young children's physical development, attention, and executive functioning (Galantino, Galbavy, & Quinn, 2008; Jensen & Kenny, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“… Metacognitive processes activity Metacognitive skills and regulation of cognition Metacognitive processes and attentional of recreational endurance runners. 8 [ 52 ] Investigate teachers’ perceptions of yoga in a school setting. Self-Regulation and Behavioral Benefits Self-regulation skills: take deep breaths to calm and relax the body, calmness Physical development, self-regulation skills, and social-emotional skills, behavioral and cognitive benefits of yoga.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Metacognitive processes activity Metacognitive skills and regulation of cognition Metacognitive processes and attentional of recreational endurance runners. 8 [ 52 ] Investigate teachers’ perceptions of yoga in a school setting. Self-Regulation and Behavioral Benefits Self-regulation skills: take deep breaths to calm and relax the body, calmness Physical development, self-regulation skills, and social-emotional skills, behavioral and cognitive benefits of yoga.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the data focus on performance in three aspects during learning processes: 6 articles (30%) focus on metacognitive processes,12 articles (60%) focus on self-regulation, and two articles (10%) focus on executive functions. The sports disciplines include soccer, 30 , 47 , 62 gymnastics, 48 endurance running, 14 , 51 , 55 golf, 49 taekwondo, 50 , 60 MMA, 54 , 56 , 61 yoga, 52 table tennis, 57 hockey, 63 and metacognition-related physical education programs. 53 , 58 , 59 , 64 Most studies indicate that metacognitive performance varies across different sports disciplines.…”
Section: Resultsmentioning
confidence: 99%
“…The implementation of yoga in class is fun, easy, and cost-effective, according to Khalsa and Butzer's (2016) review. Wolff and Stapp (2019) argued that teachers have an invaluable role in implementing yoga in schools. They found that the breathing techniques acquired during yoga increased the ability to selfregulate and improve attention.…”
Section: Introductionmentioning
confidence: 99%
“… Wolff and Stapp (2019) argued that teachers have an invaluable role in implementing yoga in schools. They found that the breathing techniques acquired during yoga increased the ability to self-regulate and improve attention.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a meta-analysis of 35 school-based contemplative practices, including static (that is, not including movement) mindfulness and mindful yoga programs (e.g., programs including static mindful breathing exercises and yoga-based movements), demonstrated a small, positive statistically significant effect on cognitive and socio-emotional outcomes (Maynard et al, 2017 ). Qualitative studies also suggested that teachers observed the social and emotional benefits their students gain from participating in contemplative practices (Dariotis et al, 2017 ; Mendelson et al, 2013 ; Wolff & Stapp, 2019 ).…”
mentioning
confidence: 99%